Further studies of a lake breeze: Part 1- Observational study (MAUSAM, 1985)
The three-dimensional structure and bebaviour of a lake-land breeze circulation system induced by lake Ontario for a selected 24-hour period is presented. The structure is   determined from observations made during the International Field Year of the Great Lakes. The case which has been studied occurred when the large scale prevailing flow was blowing from the south at relatively low speeds. The study shows that the lake induces a broad belt of easterlies over the lake in the afternoon and the early evening. It also indicates that the lake breeze; is more likely to occur over the southwestern coastal regions than over the southeastern coastal regions. During the early morning hours, surface wind convergence occurs over the northeastern shoreline but not over the northwestern shoreline.